KEBIJAKAN MORATORIUM PERIZINAN USAHA PERIKANAN TANGKAP DI WILAYAH PENGELOLAAN PERIKANAN NEGARA REPUBLIK INDONESIA 2014-2015 - Faisyal Rani; Yusfa Afrina (EcoNews, 2018)
This research would explain about Indonesia’s government policy to stop and banned the illegal fishing’s activity after Indonesia’s got many disadvantage in the fishery sector.This policy created a pro and contra for actors has illegal fishing’s activity like foreign fishing vessels and Indonesian’s fishing vessels. To see the problem of Indonesia’s Government Issuing Moratorium of Permit to Fishing Effort in the Fisheries Management Area Republic of Indonesia, the author uses a qualitative research methodology, the data collection techniques by library research are derived from sources of literature books, published magazine, journals, and scientific articles. The perspective used is Merchantilism that see the state’s role in regulating its economy. The theory used is Protectionism. Indonesia’s policy became implications for improved utilization of sources from the sea improvement of fishery management, eradication of illegal fishing and an increase in achieving economic goals such as exports that are beginning to increase again.While the implications of this policy forillegal fishing’s actors from several countries in Indonesia’s around is lessening fishing effort than usual.